Evaluation of Omega-3 Effect as Adjuvant Therapy to Methotrexate on Alkaline Phosphatase Level in Iraqi Patients with Active Rheumatoid Arthritis - Saleh Khudhur, Shaimaa (Tikrit Journal of Pharmaceutical Sciences, 2023)
Rheumatoid arthritis (RA) is a common inflammatory disease associated with many extraarticularfeatures. The aim: of the current study is to assess the influence of omega-3 fatty acids(EPA, DHA) on serum alkaline phosphatase in patients with active RA. A single blinded placebocontrolled clinical trial with 12 weeks follow up period at which 50 patients with active RAusing methotrexate were randomized into 2 groups to receive either omega-3 (1000 mg) capsulethree times daily or capsules prefilled with glucose as placebo and were evaluated at zero time(baseline) and after 12 weeks for alkaline phosphatase level in serum. In addition to twenty fivehealthy subjects as control group. The age of RA patients in omega-3 group ranged from 25-80years (50.36±2.46), whereas the age of RA patients in placebo group ranged from 35-68 years(50.08±1.84 ), while the age of apparently healthy subjects in control group where ranged from40-60 years (94.20±1.12). The RA disease activity was measured using disease activity score of28 joints(DAS28-ESR) and clinical disease activity index (CDAI). After 12 weeks of startingadjuvant treatment with either omega-3 or placebo, the results showed that there were nosignificant difference between the effect of omega- 3 and placebo on alkaline phosphatase level.In Conclusion, omega-3 significantly decreased alkaline phosphatase level in patient with activerheumatoid arthritis